Chargic representation of conflicts over the demarcation of indigenous lands in Brazil - Miani, Rozinaldo Antonio; Akamatsu, Bruna Miyuki Enomoto (Argumentum, 2024)
The issue of demarcation of indigenous lands has been one of the main areas of social and political conflicts in Brazil since the beginning of the 21st century - among them, the unfoldings in the demarcation process of the Raposa-Serra do Sol Indigenous Land and the debate around PEC 215, as well as the bill's controversies regarding the time frame. In this sense, the objective of this article is to present and reflect on the main impasses and conflicts that shaped the issue of demarcation of indigenous lands in Brazil in recent decades based on the analysis of Carlos Latuff's chargic production, following the methodology of chargic discourse analysis. The analyzes pointed to a reality permeated by violence against indigenous peoples and in favor of capitalist agribusiness interests, mainly due to the intensification of territorial expropriation.
Keywords: Land demarcation; Indigenous peoples; Territorial expropriation; Satirical cartoon; Carlos Latuff